(untitled) (Research, Society and Development, 2021)
Bizarre parostal osteochondromatous proliferation (BPOP) or also called Nora’s disease, is a rare, benign lesion whose radiographic and histological characteristics can lead to a wrong diagnosis. Most of the cases reported in the literature correspond to the small tubular bones of the hands and feet, being the involvement of the skull and jaws extremely rare. Treatment is surgical and includes surgical excision, simple resection and resection with wide margins; the lesion presents high recurrence (50%) for this reason, when it occurs in small bones such as metacarpals, total amputation of the bone is chosen. Here we present a case of BPOP involving the alveolar ridge of the mandible of a 72-year-old woman. This would be the ninth published case of bizarre parostal osteochondromatous proliferation corresponding to the maxillofacial region and the fourth case located in the mandible.